Bi-functional NaBiF4: Er3+, Tm3+ nanoparticles for optical thermometry and anti-counterfeiting applications. (January 2022) - Xu, Meimei; Ge, Wanyin; Zhang, Xinmeng; Li, Yongxiang
Graphical abstract: The spherical NaBiF4 :0.2Er 3+, xTm 3+ (0.01, 0.02, 0.04, 0.2) nanoparticles were successfully prepared by an environmental-friendly route. The temperature sensing abilities and anti-counterfeiting properties were studied in detail under excitation of 980 nm laser. Highlights: The NaBiF4 :0.2Er 3+, xTm 3+ samples were prepared by an environmental-friendly route. The temperature sensing and anti-counterfeiting properties were discussed. The maximum Sr (1.31 % K −1 ) and Sa (1.53 % K −1 ) were obtained at 293 K. Abstract: Very recently, NaBiF4 based hosts have evoked considerable interest due to a series of unique advantages. However, the current synthesis methods employed ethylene glycol (EG) as the solvent, which may cause the surrounding-related pollution problems due to the toxicity of EG solvent. Herein, we presented a green, efficient, and environmentally friendly approach to obtain NaBiF4 NPs matrix in the solvent of ethanol substituting the toxic EG. A series of NaBiF4 : 0.2Er 3+, xTm 3+ (x = 0, 0.01, 0.02, 0.04, 0.2) nanoparticles (NPs) were successfully prepared. The obtained NPs exhibit tunable colors from green to red with the increasing of Tm 3+ concentration. Furthermore, take the NaBiF4 : 0.2Er 3+, 0.02Tm 3+ compound as an example, the temperature sensing performance was investigated ranging from 298 to 478 K. Not only a high Sa (1.53%) but also superior Sr (1.31%) are simultaneously obtained at 298 K, providing an ideal optical temperature sensor. Meanwhile, to expand the applications, the anti-counterfeiting properties were studied on different substrates. The results show our green synthesis route is feasible and NaBiF4 : 0.2Er 3+, xTm 3+ phosphor has high potential in the optical temperature sensors and anti-counterfeiting applications.